Reliability and validity of a physical activity social support assessment scale in adolescents - ASAFA Scale - José Cazuza de Farias Júnior; Gerfeson Mendonça; Alex Antonio Florindo; Mauro Virgilio Gomes de Barros (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
Objective: To analyze the reliability and validity of a scale used to measure social support for physical activity in adolescents - ASAFA Scale. Methods: This study included 2,755 adolescents (57.6% girls, 16.5 ± 1.2 years of age), from Joao Pessoa, Paraiba, Brazil. Initially, the scale was consisted of 12 items (6 for social support from parents and 6 from friends). The reliability of the scale was estimated by Cronbach's alpha coefficient (α), by the Composite Reliability (CR), and by the model with two factors and factorial invariance by Confirmatory Factor Analysis (CFA) adequacy. Results: The CFA results confirmed that the social support scale contained two factors (factor 1: social support from parents; factor 2: social support from friends) with five items each (one item was excluded from each scale), all with high factor loadings (> 0.65) and acceptable adjustment indexes (RMR = 0.050; RMSEA = 0.063; 90%CI: 0.060 - 0.067); AGFI = 0.903; GFI = 0.940; CFI = 0.934, NNFI = 0.932). The internal consistency was satisfactory (parents: α ≥ 0.77 and CR ≥ 0.83; friends: α ≥ 0.87 and CR ≥ 0.91). The scale's factorial invariance was confirmed (p > 0.05; Δχ2 and ΔCFI ≤ 0.01) across all subgroups analyzed (gender, age, economic class). The construct validity was evidenced by the significant association (p < 0.05) between the adolescents physical activity level and the social support score of parents (rho = 0.29) and friends (rho = 0.39). Conclusions: The scale showed reliability, factorial invariance and satisfactory validity, so it can be used in studies with adolescents.